Writing a wrong - Hechtman, Betty, 1947- (Hechtman, Betty, 1947- Writer for hire mystery, 2021)
As a writer for hire, Veronica Blackstone puts her keyboard to use to help others. That includes writing advertising copy for local businesses, and love letters for those needing romantic help. Tony Richards needs the latter. Debonair, charismatic, handsome, Tony seems like the last person who'd need help with love letters, but help him Veronica does... only, Tony owes her money and won't tell her anything about the woman she's writing the love letters for. That's not how Veronica normally works. When Tony is found dead, his real name is revealed as Ted Roberts. The police think his death was part of a burglary gone wrong, but Veronica isn't convinced. Why did he lie about his name? Who were the love letters for? And could they hold the key to his death?